2023
DOI: 10.3389/fonc.2023.1054594
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of nomograms for predicting survival in differentiated thyroid cancer patients with or without radioiodine therapy

Abstract: ObjectiveThis study aimed to establish and validate the nomograms for predicting overall survival (OS) probabilities in differentiated thyroid cancer (DTC) patients who received and did not receive radioiodine therapy (RAI), respectively.MethodsIn this study, 11, 099 patients diagnosed with DTC in the Surveillance, Epidemiology, and End Results (SEER) database from 2004 to 2016 were selected. Whether they have RAI, they are divided into RAI (n=6427) and non-RAI (n=4672) groups. They were randomly assigned to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Numerous factors influence LNM in EGC, and the identified risk factors differ across studies. Consistently, the depth of tumor invasion and tumor size are significant predictors of LNM across almost all research[ 9 , 21 , 26 , 27 ]. Based on preoperative clinicopathological data, we identified risk factors for LNM in EGC patients, and the results showed that tumor size, tumor location, degree of differentiation and pathological type were independent predictive risk factors for LNM in EGC patients.…”
Section: Discussionmentioning
confidence: 62%
“…Numerous factors influence LNM in EGC, and the identified risk factors differ across studies. Consistently, the depth of tumor invasion and tumor size are significant predictors of LNM across almost all research[ 9 , 21 , 26 , 27 ]. Based on preoperative clinicopathological data, we identified risk factors for LNM in EGC patients, and the results showed that tumor size, tumor location, degree of differentiation and pathological type were independent predictive risk factors for LNM in EGC patients.…”
Section: Discussionmentioning
confidence: 62%
“…Inclusion criteria were: (1) Those who signed the informed consent before CEUS examination; (2) The nodules could be completely displayed in one section on US; (3) The final pathological results after surgical excision were obtained. Exclusion criteria were the following: (1) CEUS showed no enhancement; (2) CEUS images were not clear; (3) The distance between the edge of the nodule (>50%) and the thyroid capsule was <3 mm.…”
Section: Patientsmentioning
confidence: 99%
“…Differentiated thyroid cancers (DTC) (1)including papillary thyroid carcinoma (PTC), follicular thyroid carcinoma (FTC), and their variant subtypes (2), are the most frequent endocrine malignancies, and the incidence increased rapidly in recent years. DTC usually has a good prognosis, and Iodine-131 therapy and thyroid inhibitors have been shown to be beneficial for patients 10year survival rates ranging from 80 to 95 percent (3,4). However, about 5%-20% of cases may have tumor biological variation due to gene mutation, resulting in different subtypes and poor prognosis, which may be related to the biological characteristics of highly invasive tumors (5).…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been many studies globally on the characteristics and regularity of LNM in EGC, but there is still no accurate prediction model. An increasing number of scholars believe that nomograms are effective tools for predicting tumour progression and aiding clinical decision-making [5][6][7][8][9][10] Prediction models are widely used to predict diagnosis and evaluate prognosis [11,12] , tumour stage, recurrence, metastasis, patient survival, and therapeutic e cacy [13][14][15][16][17][18] , There have been numerous studies worldwide on nomograms for the prediction of LNM in EGC [19][20][21] . Cui [22] et al established a nomogram for predicting LNM in EGC, which included patient sex, tumour morphology, vascular invasion, lymphangiosarcoma thrombosis, tumour length, tumour invasion depth, and tumour differentiation degree.…”
Section: Introductionmentioning
confidence: 99%